Treatment of advanced invasive Thymomas in experience of Oncology Department at Regional Centre of Lung Diseases in Poznań and Department of Thoracic Surgery, Poznań University of Medical Sciences - Ramlau, Rodryg; Bryl, Maciej; Dyszkiewicz, Wojciech; Pieluchowski, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2006)
Introduction: Thymoma is a rare neoplasm, deriving from epithelial tissue of Thymus. ADOC, PAC, PE and VIP are most frequently used combintions. Materials and method: Retrospective analysis including 13 patients treated with chemotherapy between 1995 and 2004. Mean age was 40 years (18-55). Performance status: 8 patients in PS-1 and 5 in PS-2 (ECOG). Histologic types A/AB/B1/B2/B3 – 1/2/1/4/5 respectively and clinical stages: II°/III°/IVA°/IVB° – 2/7/3/1 respectively. Chemotherapy was given as: adjuvant one – 4 cases (3 – III° and 1 – II°), induction treatment in 3 cases (II° and III°), remaining 6 cases due to inoperable disease (2 in III°, 3 in IVA° and 1 in IVB°). Results: In first line following regimens were used: PAC – 2, VIP – 8, ADOC – 3 cases. Radiotherapy was implemented in 8 patients: paliatively: 2 – Superior Vena Cava Syndrome, 1 – bone metastases, radicaly: 1 – adjuvant therapy, 2 – interdisciplinary treatment (induction chemotherapy + surgery + adjuvant radiotherapy), and 2 – combined treatment. In 2 cases ADOC regimen was implemented in second line treatment. Objective response – first line 70% (1 CR and 6PR), second line – 100% (1 PR and 1 CR). Conclusion: Systemic treatment of patients with thymoma leads to achievement of significant response rate. Such treatment can be implemented as an adjuvant one, as an induction therapy and as a part of combination treatment as well as alone one. In case of recurrence it is possible to consider second line treatment and achieve satisfactory clinical improvement and objective response. Massive mediastinum involvement should lead to consideration of prophylactic antithrombotic treatment.